2022
DOI: 10.32598/bcn.12.6.2062.1
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline Improves Memory by Enhancing Hippocampal Synaptic Plasticity and Restoring Antioxidant Enzyme Activity in a Rat Model of Cerebral Ischemia-Reperfusion

Abstract: Introduction: Oxidative stress plays a crucial role in the impairment of synaptic plasticity following cerebral ischemia which ultimately results in memory dysfunction. Hence, application of antioxidant agents could be beneficial in the management of memory deficit after brain ischemia. Minocycline is a tetracycline antibiotic with antioxidant effect. The main objective of this work was to assess minocycline effect on the impairment of synaptic plasticity and memory after cerebral ischemia-reperfusion in rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Duration and dose of scopolamine injection were determined according to recent investigations [ 19 , 22 , 21 ]. The treatment groups (groups 3–6) received 10, 15, 20, or 30 mg/kg of minocycline, whereas the scopolamine group and group 1 received the vehicle for two weeks [ 23 , 10 ]. During the third week, the treatment groups received minocycline (10, 15, 20, and 30 mg/kg), whereas groups 1 and 2 received vehicle 1 h before performing the behavior tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Duration and dose of scopolamine injection were determined according to recent investigations [ 19 , 22 , 21 ]. The treatment groups (groups 3–6) received 10, 15, 20, or 30 mg/kg of minocycline, whereas the scopolamine group and group 1 received the vehicle for two weeks [ 23 , 10 ]. During the third week, the treatment groups received minocycline (10, 15, 20, and 30 mg/kg), whereas groups 1 and 2 received vehicle 1 h before performing the behavior tests.…”
Section: Methodsmentioning
confidence: 99%
“…In the previous studies, minocycline was found to attenuate cognitive impairment, which is linked to its anti-neuro-inflammatory and anti-apoptotic activities [ [7] , [8] , [9] ]. For instance, a previous study indicated that minocycline alleviated passive avoidance performance and long-term potentiation in a rat model of cerebral ischemia-reperfusion, possibly by modifying synaptic plasticity and oxidative stress state [ 10 ]. Minocycline was also found to induce beneficial effects against streptozotocin-induced brain injury [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this background, we speculated that ferroptosis may play role in microglial death during CIRI. Minocycline (Mino), a semisynthetic tetracycline derivative, has acute neuroprotective effects mainly through anti-in ammatory, antioxidant, and neurogenesis effects, especially microglial activation and polarization [13][14][15]. However, whether minocycline has an effect on microglial death remains unclear.…”
Section: Introductionmentioning
confidence: 99%